Endoscopic resection of giant esophageal fibrovascular polyp - Khamaysi, Iyad; Asbeh, Yousef Abu (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Khamaysi I, Asbeh YA. Endoscopic resection of giant esophageal fibrovascular polyp. Turk J Gastroenterol 2020; 31(3): 276-8.